Description of the first zoeal stage of Synalpheus apioceros Coutière, 1909 (Caridea: Alpheidae), including a comparative analysis with larval morphology from the genus Synalpheus Spence Bate, 1888 - Santos, Rafael C.; Pescinelli, Régis A.; Costa, Rogerio C. (Zootaxa, 2020)
Herein, the Zoea I of Synalpheus apioceros is described, followed by a comparative analysis of the first larval stage from Synalpheus. Larvae were obtained from two ovigerous females sampled in Ubatuba, São Paulo. The morphology of the Zoea I of S. apioceros was compared to five other Synalpheus species whose structures were previously described: S. biunguiculatus, S. minus, S. neomeris, S. pectiniger, and S. tumidomanus. A set of unique morphological characteristics was found for S. apioceros: exopod of antennule with 4 aesthetascs and 1 plumose seta; coxal endite of maxillule with 2 simple setae plus 2 plumose setae; basial endite of maxillule with 2 simple setae plus 2 short spines; endopod of maxillule with 1 plumose seta plus 2 simple setae; basial endite of maxilla bilobed with 2 (1 plumose and 1 simple) + 2 (1 plumose and 1 simple) setae; coxal endite of maxilla bilobed with 2 + 1 plumose setae; endopod of maxilla with 3 (1 plumose and 2 simple) terminal setae + 2 simple setae; endopod of first maxilliped unsegmented with 3 terminal simple setae; basis of first maxilliped with 5 spines; endopod of second maxilliped 5-segmented with 0, 0, 0, 1 plumodenticulate, 4 (1 serrate + 3 simple) setae; endopod of third maxilliped 5-segmented with 0, 0, 0, 1 simple, 3 simple setae; pereiopods 1st to 3rd birramous and 4th and 5th uniramous. S. apioceros shows higher morphological similarity with S. minus, followed by S. tumidomanus, S. neomeris and S. pectiniger, probably since these species present extended larval development. Besides the similar morphology among species, the unique attributes presented here are important for the genus’ taxonomy, being fundamental for identifying the first larval stages of Synalpheus, as well as for subsidizing information for species identification keys.